1989
DOI: 10.1007/bf00445753
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of a split chloroplast gene from mustard (Sinapis alba): ribosomal protein gene rps16 reveals unusual transcriptional features and complex RNA maturation

Abstract: The mustard chloroplast gene rps16 is split by an 887 bp group II (or III) intron. Three RNA 5' ends upstream of the rps16 coding region define both the transcription start site and two RNA processing sites. The DNA region preceding the start site contains a procaryotic-type "-10" promoter element, but not a typical "-35" element. One single RNA 3' end has been detected downstream from the rps16 coding region, but it is not in close proximity to any inverted repeat that might serve as a termination signal. Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…The promoters of these latter genes contain -10 and -35 elements homologous to cis-elements in prokaryotic sigma-70 promoters (for a review, see Hanley-Bowdoin and Chua, 1987). In contrast, the presumptive promoters of rpoB (Hudson et al, 1988) and rpsl6 (Neuhaus et al, 1989) are AT-rich and lack these elements. On the other hand, the trnK (Boyer and Mullet, 1988b) and 16s rRNA (Sun et al, 1986;Baeza et al, 1991) promoters contain -10 and -35 elements.…”
Section: Differential Transcription Of Rpob 16s Rrna Frnfm/c and Tmentioning
confidence: 93%
“…The promoters of these latter genes contain -10 and -35 elements homologous to cis-elements in prokaryotic sigma-70 promoters (for a review, see Hanley-Bowdoin and Chua, 1987). In contrast, the presumptive promoters of rpoB (Hudson et al, 1988) and rpsl6 (Neuhaus et al, 1989) are AT-rich and lack these elements. On the other hand, the trnK (Boyer and Mullet, 1988b) and 16s rRNA (Sun et al, 1986;Baeza et al, 1991) promoters contain -10 and -35 elements.…”
Section: Differential Transcription Of Rpob 16s Rrna Frnfm/c and Tmentioning
confidence: 93%
“…To obtain the sequences encoding rps16 in the Brassicaceae chloroplast genomes, we conducted a BLASTN search using the sequence of the cp rps16 gene of Arabidopsis thaliana as the query. The results identified 11 complete Brassicaceae chloroplast genomes (GenBank accession numbers: Aethionema grandiflorum, AP009367; Arabis hirsuta, AP009369; Barbarea verna, AP009370; Brassica rapa subsp pekinensis, AC189190; Capsella bursa-pastoris, AP009371; Crucihimalaya wallichii, AP009372; D. nemorosa, AP009373; Lepidium virginicum, AP009374; L. maritima, AP009375; Nasturtium officinale, AP009376; O. pumila, NC_009267) and the partial chloroplast genome, including rps16, of Sinapis alba (GenBank accession number: X13609) (Neuhaus et al, 1989). A comparison of these sequences revealed that the rps16 genes in the Aethionema grandiflorum, Arabis hirsuta, D. nemorosa, and L. maritima chloroplast genomes have become pseudogenes.…”
Section: Pseudogenization Of Rps16 In the Chloroplast Genomes Of Somementioning
confidence: 99%
“…these promoter elements. In contrast, the rps76 promoter lacks -35 sequence elements but retains a -10-like domain (Neuhaus et al, 1989). Moreover, transcription of rrnR7 and frnS7 does not require any upstream sequences (Gruissem et al, 1986).…”
Section: Introductionmentioning
confidence: 99%